Numerical simulation on effects of pore characteristics on strength in porous ceramics - Natsumi MIYAZAKI (The Japan Society of Mechanical Engineers, 2019)
Porous ceramics are expected to be applied as filters, catalysts, etc. in energy related structures, because they have higher heat-resistance and larger specific surface area. Even for such functional applications, their strength should be adequately evaluated to guarantee long-term durability with fulfilling the required functions. However, it is very difficult to investigate strength for porous ceramics with various pore characteristics experimentally. In this work, an analytical procedure was proposed for estimating strength in porous ceramics by taking account of the pore characteristics, such as porosity, pore density and pore radius. In the procedure, porous ceramics were assumed to have the same characteristics of crack distribution as those of pore distribution, and pores were presumed to be surrounded by virtual cracks. For several materials with different pore characteristics, numerical simulations based on the proposed procedure were carried out to estimate their strength and to clarify effects of pore characteristics on strength. It was reconfirmed that the strength of porous ceramics had a general tendency to decrease drastically as increasing porosity. It was also revealed that the strength of porous ceramics were affected by porosity, pore density and average pore radius, respectively. Based on the simulated results, it was suggested that porous ceramics with higher strength can be obtained by including many small pores in producing porous ceramics with a predetermined bulk porosity. In other words, for porous ceramics with the same bulk porosity, various strength characteristics can be attained by controlling the pore size.